Is it difficult to obtain inter-observer agreement in the measurement of the beta angle in ultrasound evaluation of the paediatric hip? - (:unkn) unknown (BMC, 2019)
Introduction: The aim of this study was to determine the differences and consistencies in the morphological and angular interpretations of standard USG images. Therefore, it was aimed to show the correlations of orthopaedic doctors with different periods of experience in hip ultrasound measurements taken with the Graf method. Materials and methods: The study included 210 infants randomly selected from those who presented at our hospital for DDH screening. A total of 6 ultrasound images were taken for each hip. These images were evaluated by two paediatric orthopaedic professors, two orthopaedic specialists and two orthopaedic residents. The correlations of these measurements between all the doctors were evaluated statistically. Results: In beta angle evaluation, agreement between all the evaluators was at the level of 0.054. No agreement was seen between the two residents or between the two specialists (p=0.003, p=0.998, p=0.998, respectively). Agreement between the two professors was determined at the level of 0.508 (p<0.001). Agreement was determined at the level of 0.066 between the specialists and the residents. No agreement was observed between the specialists and the professors or between the professors and the residents (p=0.014, p=0.098, p=0.737, respectively). Conclusions: It can be concluded that greater emphasis on the beta angle, the cartilage labrum, and more detailed explanations of this subject in the resident training program will achieve standardisation on this subject, and this is in direct proportion to clinical experience.
Keywords: Congenital hip dysplasia; Ultrasonography; Beta angle; Graf method; DEVELOPMENTAL DYSPLASIA; ULTRASONOGRAPHY; DIAGNOSIS; CLASSIFICATION; INFANTS; GRAF; RISK